Mejorar el proceso de planeación, programación y control de la producción en una empresa de recubrimiento de rodillos en caucho - Bedoya Giraldo, Valentina (Universidad de San Buenaventura, Cali, 2019)
The company dedicated to the coating of rubber rollers is a manufacturing company, which has been in the market for more than 15 years in the market and works under the modality make to order, before starting the project there were problems in the delivery fulfillment of the orders, due to the fact that according to their installed capacity they can deliver in about 15 days and during the year 2017 they handled on average 26 days of delivery, therefore it led the authors to design a strategy for the implementation of the planning, programming and control models of production, so that the project ended with a reduction in delivery times of up to 12 days, thus achieving its business objective of being more flexible to change and achieve greater effectiveness in its internal functioning. The project was divided in three stages, the first one was the identification of the process variables variables (definition of product groups, standard times, scheduled available hours, among others), restrictions and conditions for the design of the planning, scheduling and control process of production. The second stage is based on designing the process of planning, scheduling and control of production with the help of the Excel tool, applying the sequencing rules, the implementation of the MPS and production report formats. The third stage involves the implementation of the designs and the measurement of the results obtained. As a result of the implementation is the weekly production program with a percentage of compliance; as regards the main objective, there is a reduction in delivery times for orders from 26 days to 14 days. As a continuous improvement project it was possible to measure the productive processes by means of the implementation of the management indicators, such as quality, availability and efficiency for each job, also under a production control during the three months observed the increase of the performance by 15%, quality by 3% and availability by 2%.